2000
DOI: 10.1016/s0735-1097(00)00846-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiogenic shock due to acute severe mitral regurgitation complicating acute myocardial infarction: a report from the SHOCK Trial Registry

Abstract: The data highlight opportunities for early identification and intervention to potentially decrease the devastating mortality and morbidity of severe post-myocardial infarction MR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
135
0
16

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(156 citation statements)
references
References 15 publications
5
135
0
16
Order By: Relevance
“…Firstly, it is rare for cardiogenic shock to develop only a few hours after the onset of symptoms; the highest risk of shock is normally two to seven days after the myocardial infarction, when healing has begun. 5 In this particular patients. 10 However, Monin et al found that only 5% of patients required transoesophageal echocardiography to adequately quantify the severity of mitral insufficiency.…”
Section: Discussionmentioning
confidence: 73%
“…Firstly, it is rare for cardiogenic shock to develop only a few hours after the onset of symptoms; the highest risk of shock is normally two to seven days after the myocardial infarction, when healing has begun. 5 In this particular patients. 10 However, Monin et al found that only 5% of patients required transoesophageal echocardiography to adequately quantify the severity of mitral insufficiency.…”
Section: Discussionmentioning
confidence: 73%
“…Mitral regurgitation classically courses with acute left heart failure with important pulmonary congestion 14 , which is very dissimilar from the patient's clinical evolution, being highly unlikely.…”
Section: E71mentioning
confidence: 97%
“…A Surgical Case of Papillary Muscle Rupture after Acute Myocardial Infarction with Cardiogenic Shock Akira SEZAI 1, 3) , Kenji AKIYAMA 1, 3) , Seiji FUKUSHIMA 2,4) , Satoshi KASHIWAZAKI 1, 3) , Ayako TAKASAKA 1, 3) , Motomi SHIONO 3) , Yasutaka TAKAGI 2,4) , Masaaki NAGASHIMA 2,4) , Toshiyuki TANAKA 2,4) , Takaharu YAHATA 2,4) , Yasuo WATANABE 2, 4) , Rikitake KOGAWA 2,4) , Toru OSHIMA 2,4) , Atsushi HIRAYAMA 4) and Hitoshi KANAYA Papillary muscle rupture is considered to be one of the least frequently observed complications of acute myocardial infarction (AMI) and has a significantly high mortality. We report a case of a patient who survived due to an emergency surgery for papillary muscle rupture after AMI with cardiogenic shock.…”
Section: )mentioning
confidence: 99%